WRITE TO HEAL: GENDER-BASED VIOLENCE AND RECOVERY WITHOUT ACCOUNTABILITY IN AURÉLIE MOEREMANS’ MEMOIR BROKEN STRINGS - Latumeten, Anna Anganita Theresia; Janah, Ulum (Prologue: Journal on Language and Literature, 2026)
This study examines the representation of gender-based violence (GBV) and its aftermath in Broken Strings (2025) by Aurélie Moeremans, with particular focus on child grooming and the narrative construction of “healing” or recovery. This is a descriptive qualitative study, with the analysis grounded in feminist theoretical frameworks. The findings reveal that abuse in the memoir unfolds as a gradual and processual form of violence, characterized by manipulation, coercion, and the erosion of agency. The narrative further demonstrates how silencing is actively produced through psychological control, while failures of institutions, family, and media contribute to the persistence of harm. As the text progresses, a tonal shift toward healing and self-reclamation positions recovery as the primary form of resolution. However, this emphasis simultaneously exposes the absence of accountability, as the perpetrator remains unpunished and institutional justice inaccessible. The study argues that while the memoir foregrounds survival and resilience, it also reflects a broader tendency within GBV narratives to displace responsibility onto survivors. In doing so, Broken Strings highlights the tension between recovery and justice, raising critical questions about how violence is ultimately resolved within contemporary survivor discourse.